2015
DOI: 10.1007/s13659-015-0068-0
|View full text |Cite
|
Sign up to set email alerts
|

Brown Algae (Phaeophyceae) from the Coast of Madagascar: preliminary Bioactivity Studies and Isolation of Natural Products

Abstract: Eight species of brown algae (Phaeophyceae) from the coast of Madagascar have been investigated for their chemical constituents. Fucosterol (3) was obtained as the most abundant compound. The brown alga Sargassum ilicifolium was the source for the first isolation of the terpenoid C27-alcohol 1,1′,2-trinorsqualenol (1) from marine sources. From S. incisifolium we isolated the highly unsaturated glycolipid 1-O-palmitoyl-2-O-stearidonoyl-3-O-β-D-galactopyranosylglycerol (4) and we report the first full assignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…In continuation of our studies on the chemical constituents of marine organisms from the coast of Madagascar including red algae, 1 brown algae, 2 and soft corals, 3 we herein turned our attention to soft corals of the species Sarcophyton stellatum, Capnella fungiformis, and Lobophytum crassum. A sponge of the species Pseudoceratina arabica has also been included in the present investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our studies on the chemical constituents of marine organisms from the coast of Madagascar including red algae, 1 brown algae, 2 and soft corals, 3 we herein turned our attention to soft corals of the species Sarcophyton stellatum, Capnella fungiformis, and Lobophytum crassum. A sponge of the species Pseudoceratina arabica has also been included in the present investigation.…”
Section: Introductionmentioning
confidence: 99%
“…is acid resistant, salt-tolerant and can survive at infective levels in many types of foods such as fruits and vegetables, low pH foods, prepared foods and foods held in a modified atmosphere or vacuum packaging [ 85 ]. Studies involving brown algal extracts against S. flexneri were conducted [ 76 , 88 ] and the majority of the tested algae species belonged to the Sargassum taxa, as shown in Table 2 . From observing Table 2 , we can notice that all the antimicrobial test results were attained by Kirby–Bauer test and presented no quantitative results.…”
Section: Antibacterial Potential Of Bioactive Compounds From Macromentioning
confidence: 99%
“…Relating to Phaeophytha phylum, Sargassum spp. was the most studied genus [ 41 , 57 , 73 , 76 , 99 , 118 , 129 , 130 ]. Comparing solvent performance for bioactive compounds extraction, the following results were obtained: ethanol or acetone > crude extract or MeOH/DCM for D. membranacea [ 28 ], EtOAc > EtOH > hexane, DCM, n-BuOH, water (H 2 O) for E. cava [ 109 ]; EtOAc > DCM, BuOH> hexane > MeOH for E. bicyclis [ 121 ]; H 2 O > MeOH, acetone or ethyl acetate for F. serratus [ 131 ]; ethanol > hexane > H 2 O for H. elongata [ 21 ]; ethylacetate > MeOH for P. antillarum and P. boergeseni [ 66 ]; MeOH > acetone for S. platycarpum and for S. latifolium [ 118 ].…”
Section: Antibacterial Potential Of Bioactive Compounds From Macromentioning
confidence: 99%
“…The structural identification of compounds 1-3 was performed by 1 H and 13 C NMR analyses, and the data were compared with literature values. Accordingly, the molecules isolated were identified as saringosterol (1) [14,25,26], phytol (2) [27,28], and fucosterol (3) [14,22,29] (see Supplementary Materials).…”
Section: Structure Elucidation Of the Isolated Compoundsmentioning
confidence: 99%
“…While, as another abundant compounds family present in S. horneri, the development of sterol-related health care products is relatively slow. In fact, studies have shown that phytosterols have a wide range of biological activities and have important properties such as antibacterial, antiviral, antioxidant, and so on [9][10][11][12][13][14]. Recently, fucosterol and saringosterol (see Figure 1) were evaluated for their effects on LXR-mediated transactivation and target gene expression in six cell lines.…”
Section: Introductionmentioning
confidence: 99%